2019
DOI: 10.3390/math7121184
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Analysis on Strategies in “Main Manufacturer–Supplier” Mode Considering Technology Docking and Price Concluding under Competition Condition

Abstract: This paper analyses the strategies of the substitutable suppliers competing to collaborate with a main manufacturer in "main manufacturer-supplier" (M-S) mode. In the research and development (R&D) of complex products, only one supplier can be chosen for one kind of part as a long-term collaboration partner with the manufacturer. The competition between substitutable suppliers focuses on the technology docking and price-concluding strategies. In this paper, one original supplier as the first-mover and one new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Li et al further studied ecological compensation in the Taihu Basin of China [40]. Evolutionary game theory also provides a practicable research tool for the study of patterns of cooperation among manufacturers and suppliers in supply chain management [41,42]. For PPP projects, during their long life-cycle, the government and private sector cooperate around a unified project goal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al further studied ecological compensation in the Taihu Basin of China [40]. Evolutionary game theory also provides a practicable research tool for the study of patterns of cooperation among manufacturers and suppliers in supply chain management [41,42]. For PPP projects, during their long life-cycle, the government and private sector cooperate around a unified project goal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…EGT is dedicated to research based on the idea that players cannot fully grasp the entirety of the information, and their decision-making will change based on updated knowledge 13,14 . This kind of game theory has achieved success in research on different social fields, such as vaccine dilemma 15 , sustainable energy development 16 , environmental pollution 17 , sustainable tourism 18 , rights 19 , and Social physics 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Literature [23] established a dual channel supply chain revenue model with retailers as the main body and found that the uncertainty of demand will affect channel pricing. Literature [24] established the demand function related to price and demand, compared the optimal pricing problem under the manufacturer Stackelberg game and the manufacturer retailer Bertrand game, and found that the manufacturer in the Bertrand game decision-making mode has the highest price. Literature [25][26][27][28][29][30][31] mainly constructed a closed-loop supply chain network equilibrium model based on the dynamic competition of retail enterprises and studied the behavior and equilibrium conditions of manufacturers, retailers, and demand market.…”
Section: Introductionmentioning
confidence: 99%